Parent psychological flexibility in the context of pediatric pain: Brief assessment and associations with parent behaviour and child functioning. (14th May 2019) - Timmers, Inge; Simons, Laura E.; Hernandez, Jessica M.; McCracken, Lance M.; Wallace, Dustin P.
Abstract: Background: The parent's role in the context of pediatric chronic pain is essential. There is growing evidence that parent psychological flexibility positively impacts child functioning. To assess parents' abilities to respond with psychological flexibility to their child's pain, the Parent Psychological Flexibility Questionnaire (PPFQ) was developed. Here, we aim to validate the 10‐item version of the questionnaire in an English‐speaking population and to evaluate associations with parent behaviour, child pain acceptance and functioning. Methods: Five hundred and seventy‐eight parent‐child dyads presenting at a pediatric pain clinic were included (92% mothers, average child age 15.2 ± 1.6 years). The PPFQ was completed by the parent. Parent and child also completed other standardized questionnaires. In addition to confirmatory factor analysis and assessments of reliability and validity of the PPFQ‐10, a mediation analysis was performed to examine the direct and indirect effects of parent psychological flexibility on child functioning. Results: Confirmatory factor analysis supported the three‐factor model with subscales for Values‐Based Action, Pain Willingness and Emotional Acceptance, and the PPFQ‐10 demonstrated strong psychometric properties. After controlling for child pain, parent psychological flexibility indirectly affected child functioning through its association with both parent behaviour (i.e., protectiveness) and child pain acceptance. Conclusions: Our findings provide further support for use of the PPFQ‐10 and the importance of assessing and addressing parent psychological flexibility in the context of child chronic pain. Our data show that parent psychological flexibility has an important adaptive role and can impact child functioning through two different routes, both of which can be actively targeted in treatment. Significance: Our findings demonstrate that the PPFQ‐10 is an efficient measure of parent psychological flexibility, demonstrating strong psychometric properties. Furthermore, our analyses showed that parent psychological flexibility indirectly affects child functioning through associations with both adaptive parent behaviour and child functioning. Taken together, this study furthers the understanding of how parent psychological flexibility operates and affects children with chronic pain, and may inform and optimize treatments aimed at improving functioning by addressing child and parent coping.